SISTEM MONITORING IOT BOBOT MUATAN DAN LIVE TRACKING PADA KENDARAAN PENGANGKUT TBS BERBASIS MQTT-NEXTJS - Muhammad Hatta Ridho; Andi Prayogi; Ratu Mutiara Siregar (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2026)
The development of Internet of Things (IoT) technology provides opportunities for to improve the efficiency of Fresh Fruit Bunches (FFB) transportation in oil palm plantations. Common challenges include difficulties in monitoring vehicle locations in real time and recording load weights manually. This study aims to design and develop a load weight monitoring and live tracking system for an FFB transportation vehicle prototype using an ESP32 microcontroller, an HX711 Load Cell sensor, a Neo-6M GPS module, the Message Queuing Telemetry Transport (MQTT) protocol, and a NextJS-based monitoring dashboard. The research methodology included hardware design, software development, system integration, and functional testing. The Load Cell sensor measured the load weight, while the GPS module obtained real-time vehicle coordinates. The ESP32 processed the collected data and transmitted them via MQTT to a broker and database for visualization on the dashboard. The test results showed that the system successfully monitored load weight and tracked the prototype vehicle in real time, achieving a 100% data transmission success rate under normal network conditions. The developed system provides effective, accurate, and integrated transportation monitoring, improving the efficiency of FFB transportation management in oil palm plantations.